Effect of ductile layers in mechanical behaviour of TiAlN thin coatings - Castanho, J. M. (2003)
TiAlN is a very popular coating for high-speed cutting manufacturing processes. Nevertheless, it is important to develop research work concerning the durability of this kind of coatings. Design and producing coatings based on TiAlN with interlayers of metal with low elastic modulus, like Al, Ti or Cu may contribute to improvement of cutting efficiency. Interlayers with 80 nm of thickness, in alternateness with TiAlN with different periods were sputtered. In general, the hardness and Young's modulus of the multilayer coatings had slight smaller values, but similar relations of H/E in monolithic TiAlN coatings. However, in multilayers based on Al and Cu there is an important decrease in the H2/E ratio. Moreover, the adhesion Lc2 values of scratch test show an important increase, particularly in Al and Ti interlayers, which can be considered as an important contribution in the improvement of the cutting performance of TiAlN-based coatings.